Human papillomavirus in young women with Chlamydia trachomatis infection 7 years after the Australian human papillomavirus vaccination programme: a cross-sectional study. Issue 11 (November 2015) - Chow, Eric P F; Danielewski, Jennifer A; Fehler, Glenda; Tabrizi, Sepehr N; Law, Matthew G; Bradshaw, Catriona S; Garland, Suzanne M; Chen, Marcus Y; Fairley, Christopher K
Summary: Background: The national quadrivalent human papillomavirus (4vHPV) vaccination programme was launched in Australia in April, 2007. In this study, we aimed to explore the prevalence of vaccine-targeted human papillomavirus (HPV) types contained in the 4vHPV and nine-valent HPV (9vHPV) vaccines detected in young women diagnosed with chlamydia. Methods: In this cross-sectional study, we identified specimens from women aged 25 years or younger who attended the Melbourne Sexual Health Centre (Melbourne, VIC, Australia) diagnosed with chlamydia. We calculated the prevalence of 4vHPV types (6, 11, 16, and 18) and the extra five 9vHPV types (31, 33, 45, 52, and 58 alone) excluding 4vHPV types, stratified by Australian financial year (and according to the prevaccination and postvaccination periods) and self-reported vaccination status, for all women, Australian-born women, Australian-born women aged 21 years and younger, and overseas-born women. We calculated adjusted prevalence ratios using binomial log linear regression. Findings: Between July 1, 2004, and June 30, 2014, we included 1202 women. The prevalence of 4vHPV types in Australian-born women decreased during this period (HPV 6 and 11: 2004–05 nine [16%, 95% CI 8–28] of 56 vs 2013–14 one [2%, 0–9] of 57, p<0·0001; HPV 16 and 18: 17 [30%, 19–44] vs two [4%, 0–12], p<0·0001). In Australian-born women aged 21 years and younger, HPV 6 and 11 prevalence remained at 0% for all years after 2008–09, and we detected HPV 16 and 18 in 5% or less of samples for the same period. In unvaccinated Australian-born women, we noted a significant decrease in 4vHPV types from 66 (41%, 95% CI 34–49) of 160 in the prevaccination period (from July 1, 2004, to June 30, 2007) to five (19%, 6–38) of 27 in the postvaccination period (July 1, 2007, to June 30, 2014; p=0·031), but not in the 9vHPV types, excluding 4vHPV (36 [23%, 95% CI 16–30] vs seven [26%, 11–46]; p=0·805). Interpretation: The three-dose vaccination coverage was sufficient for the 4vHPV types to almost disappear in Australian-born women aged 21 years or younger within 3 years of introduction of the national HPV vaccination programme. We noted strong herd protection, with a significant decrease in the prevalence of 4vHPV in unvaccinated women. The 4vHPV vaccination programme in Australia has been successful at protecting women against 4vHPV types. Funding: Australian National Health and Medical Research Council.